Optimalisasi Peran Pustakawan dalam Membentuk Pola Pikir Masyarakat Melalui Pendidikan Informal - Korniawan, Rostamaji (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2016)
The paper describes the librarians understanding of the changing of citizens’ mindset. Its changing will influence to the enhancement of citizens lives, particularly in citizens welfare. To change the citizens’ mindset, librarians play certain roles to educate, for instance in informal education like to lift reading habit. The study is aimed to find the same perceptions among librarians to change citizens’ mindset. It is found that the librarians have the same perceptions of understanding that informal education like reading habit program was the good strategy to shape citizens’ mindset in order to make them more innovative and creative. In addition, the librarians have also figured out that reading may lead citizens to be more welfare.